Creation of High‐Performance Heterogeneous Photocatalysts by Controlling Ligand Desorption and Particle Size of Gold Nanocluster. Issue 39 (1st July 2021) - Kawawaki, Tokuhisa; Kataoka, Yuki; Hirata, Momoko; Akinaga, Yuki; Takahata, Ryo; Wakamatsu, Kosuke; Fujiki, Yu; Kataoka, Miori; Kikkawa, Soichi; Alotabi, Abdulrahman S.; Hossain, Sakiat; Osborn, D. J.; et al.
Abstract: Recently, the creation of new heterogeneous catalysts using the unique electronic/geometric structures of small metal nanoclusters (NCs) has received considerable attention. However, to achieve this, it is extremely important to establish methods to remove the ligands from ligand‐protected metal NCs while preventing the aggregation of metal NCs. In this study, the ligand‐desorption process during calcination was followed for metal‐oxide‐supported 2‐phenylethanethiolate‐protected gold (Au) 25‐atom metal NCs using five experimental techniques. The results clearly demonstrate that the ligand‐desorption process consists of ligand dissociation on the surface of the metal NCs, adsorption of the generated compounds on the support and desorption of the compounds from the support, and the temperatures at which these processes occurred were elucidated. Based on the obtained knowledge, we established a method to form a metal‐oxide layer on the surface of Au NCs while preventing their aggregation, thereby succeeding in creating a water‐splitting photocatalyst with high activity and stability. Abstract : The ligand‐desorption process during calcination was elucidated for metal‐oxide‐supported thiolate‐protected gold (Au) 25‐atom metal nanoculusters (NCs) using five experimental techniques. Furthermore, based on obtained knowledge, a method was established to form a metal‐oxide layer on the surface of Au NCs while preventing their aggregation, thereby succeeding in creating a water‐splitting photocatalyst with high activity and stability.